On the Usefulness of Two Small-Scale In Vitro Setups in the Evaluation of Luminal Precipitation of Lipophilic Weak Bases in Early Formulation Development - Patrick J. O'Dwyer; Georgios Imanidis; Karl J. Box; Christos Reppas (MDPI AG, 2020)
A small-scale biphasic dissolution setup and a small-scale dissolution-permeation (D-P) setup were evaluated for their usefulness in simulating the luminal precipitation of three lipophilic weak bases—dipyridamole, ketoconazole and itraconazole. The transition from the gastric to intestinal environment was incorporated into both experimental procedures. Emulsification during the biphasic dissolution experiments had a minimal impact on the data, when appropriate risk mitigation steps were incorporated. Precipitation parameters estimated from the in vitro data were inputted into the Simcyp® physiologically based pharmacokinetic (PBPK) modelling software and simulated human plasma profiles were compared with previously published pharmacokinetic data. Average Cmax and AUC values estimated using experimentally derived precipitation parameters from the biphasic experiments deviated from corresponding published actual values less than values estimated using the default simulator parameters for precipitation. The slow rate of transport through the biomimetic membrane in the D-P setup limited its usefulness in forecasting the rates of in vivo precipitation used in the modelling of average plasma profiles.